The Association of Olfactory Dysfunction With Depression, Cognition, and Disease Severity in Parkinson's Disease - Fang, Ting-Chun; Chang, Ming-Hong; Yang, Chun-Pai; Chen, Yi-Huei; Lin, Ching-Heng (Frontiers in Neurology, 2021)
Background Non-motor subtypes of Parkinson’s disease (PD) include the limbic, cognitive, and brainstem phenotype, which may have different pathological pathways with olfaction. In this study, we aim to clarify the association of olfactory dysfunction with depression, cognition, and disease severity in PD. Methods A total of 105 PD subjects were included and divided into anosmia and non-anosmic groups, using the University of Pennsylvania Smell Identification Test (UPSIT). All patients were evaluated with the Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS), the Beck Depression Inventory (BDI)-II, and the Montreal Cognitive Assessment (MoCA). Results The BDI-II and UPSIT scores had a trend of reverse correlation without statistical significance (β-coefficient -0.12, p=0.232). However, the odds ratio (OR) in anosmia was 2.74 (95% CI 1.01—7.46) for depression, and was 2.58 (95% CI 1.06—6.29) for cognitive impairment. For the MDS-UPDRS total and Part 3 score, the anosmia had a β-coefficient of 12.26 (95% CI 5.69—18.82) and 8.07 (95% CI 3.46—12.67). Neither depression nor cognitive impairment is associated with motor symptoms. Conclusion More severe olfactory dysfunction in PD is associated with cognitive impairment, and greater disease severity. Depression in PD may involve complex pathways, causing relatively weak association with olfactory dysfunction.